Correction of extreme premaxilla malposition in an infant with BCLP using PNAM: a case report - Andreas, Rama; Viandini, Dewi; Damayanti, Lisda (Padjadjaran Journal of Dentistry, 2025)
Introduction: Cleft lip and palate are the most common congenital abnormalities occurring in the orofacial region. Infants with this condition need to be treated as early as possible to achieve satisfactory treatment outcomes. Presurgical Nasoalveolar Molding (PNAM) is a non-surgical treatment used to reshape and realign the gingiva, lips, and nasal openings to reduce the severity of the cleft and reposition the premaxilla before labioplasty is performed. This case report aims to explain the use of PNAM to correct an extreme premaxilla malposisition that accompany complete bilateral cleft lip and palate in infants. Case Report: A month old infant came to Hasan Sadikin General Hospital with his parents with clinical conditions of complete bilateral cleft lip palate (CBCLP) and a protrusive and rotated premaxilla. PNAM was fabricated for the infant and periodic follow-ups were conducted to correct the lip and palate cleft as well as the premaxilla abnormalities to normal anatomical conditions. At the start of the treatment, the infant weighed 4.3kg, and the cleft gap measured 9mm. At the end of the treatment, the infant weight was 6.1kg, and the cleft gap was reduced to 6mm. Then the infant was referred to the Department of Oral Surgery for a labioplasty. Discussion: Managing complete bilateral cleft lip and palate (CBCLP) is challenging due to severe anatomical deformities. In this case, PNAM effectively aligned the premaxilla, reduced the alveolar cleft width from 9 mm to 6 mm, and optimized nasal cartilage molding through techniques such as lip taping and nasal stenting. Early initiation of PNAM at one month of age and a multidisciplinary approach involving paediatricians, prosthodontists, and oral surgeons ensured personalized care and improved surgical readiness. Conclusion: BCLP requires a multidisciplinary approach. This case shows PNAM's success as a standard for improved surgical outcomes, function, and aesthetics.